Evaluation Of Oxidative Stress And Antioxidant Status In Patients With Epilepsy - RAKESH MUDARADDI; RAMESH; SAMEER; AMARESHWARA M; RAVINDRA MARADI; ANIL B; BEENA V. SHETTY (International Journal of Pharma and Bio Sciences, 2011)
The main aim of this study was to evaluate the role of Plasma advanced oxidation protein product (AOPP), protein carbonyl as indicator of oxidative stress and reduced glutathione, total thiols, albumin as antioxidant status among epileptics. 25 patients with history of epilepsy on treatment in the age group of 20-60 years were compared with 25 normal healthy controls of same age group. There was highly significant increase in AOPP (P=0.002) and protein carbonyl (p=0.001), with significantly decreased antioxidants such as reduced glutathione (p=0.007), total thiols (p=0.023) and albumin (0.01) were noted among epileptics when compared to healthy controls. From this study it could be concluded that increased oxidative stress and reduced antioxidants may be associated with pathophysiology of epilepsy.